Formation of TiN Grid on NiTi by Laser Gas Nitriding for Improving Wear Resistance in Hanks' Solution. Issue 5 (May 2016) - Ng, C.H.; Chan, O.K.; Man, H.C.
Abstract : Laser gas nitriding (LGN) is a common surface modification method to enhance the wear resistance of titanium (Ti) alloys, which are known to have poor tribological properties. In the present study, a titanium nitride (TiN) grid network was fabricated on the surface of nickel titanium (NiTi) by LGN. The laser processing parameters were selected to achieve nitriding without surface melting and hence to maintain a smooth surface finish. The characteristics of the grid-nitrided samples were investigated by scanning-electron microscopy, X-ray diffractometry, optical microscopy, 2-D profilometry, contact angle measurements and nanoindentation. The wear resistance of the nitrided samples was evaluated using reciprocating wear test against ultra-high-molecular-weight polyethylene (UHMWPE) in Hanks' solution. The results indicate that the wear rates of the grid-nitrided samples and the UHMWPE counter-body in the wear pair are both significantly reduced. The decrease in wear rates can be attributed to the combination of a hard TiN grid and a soft NiTi substrate. In Hanks' solution, the higher hydrophilicity of the nitrided samples also contributes to the better performance in wear test against hydrophobic UHMWPE.